Peripheral and lung resident memory T cell responses against SARS-CoV-2 - Judith Grau-Expósito (Nature Portfolio, 2021)
Lung resident memory T (TRM) cells are important for protection from viral infection in the lungs. Here the authors use paired lung biopsy material and blood to characterize T cell responses in patients with COVID-19 over time and find persistence of antiviral lung TRM cells that might be important to limit reinfection.